Metaphors in counselor education and supervision - Stewart-Spencer, Sarah E.; Dean, Christian J. (New York, NY : Routledge, 2022)
"Metaphors in Counselor Education and Supervision provides counselor educators and supervisors with creative applications of metaphors to help students and supervisees who struggle with abstract clinical concepts or foundational clinical skills. Featuring contributions from a range of counselors and educators, this teaching and supervision guide provides a variety of metaphors to clarify different areas of counselor education and supervision, including, but not limited to, case conceptualization, self-care, the counseling process, countertransference, suicide assessments, and advocacy. Each metaphor is accompanied by ethical and cultural considerations, group supervision modifications, and alternative uses to help emphasize diversity and ethics. This book will prepare supervisees and students with unique methods for teaching and understanding counseling concepts and skills and supply professional counselors with creative and different perspectives to use in practice"--
Keywords: Counseling -- Study and teaching; Counseling psychology -- Study and teaching; Counselors -- Supervision of; PSYCHOLOGY / Psychotherapy / Counseling; EDUCATION / Counseling / General